Evaluation of antidiabetic activity of Oxalis corniculata in streptozotocin induced diabetic rats - Dutta, Arijit; Lahkar, Mangala; Handique, Chimi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Oxalis corniculata is traditionally well known for its versatile uses. The present study was carried out to evaluate the antidiabetic action of ethanolic extract of Oxalis corniculata in streptozotocin induced diabetic albino rats. Methods: To look for the antidiabetic effect the albino rats were divided into 5 groups, each consisting of 6 animals. Diabetes was induced by a single i.p. injection of streptozotocin at a dose of 50mg/kg body weight. Standard drug, glibenclamide and ethanolic extract of Oxalis corniculata (EEOC) at doses 200mg/kg and 400mg/kg body weight was fed to the rats and it was continued till the end of the study. The blood glucose levels were estimated on day 0, 3, 7, 14 and 21 day. The standard drug and the extract were fed from day 4 onwards. Results: The antidiabetic property of the extract has shown increasing trend with increase in dose and there was a gradual decrease in blood glucose levels with increased period of exposure to the test drug. Conclusions: Results obtained in this study substantiate the anti-diabetic activity of EEOC leaves.